A REVIEW STUDY ON THE IMPACT OF DIGITAL ART ON FREELANCE ART IN INDIA - Tongaria, Mukesh; Mathur, Kumkum (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present research examines the profound impact of digital technology on freelance art in India, focusing on its evolution, opportunities, and challenges. Over the past few decades, the expansion of digital tools has significantly transformed the nature of art creation and distribution. This research traces the historical origins of digital art in India, focusing on how traditional artistic practices have adapted to change with technological advancements to create new forms and modes of art expression. The study provides insight into the new opportunities digital technology has opened up for art, including access to larger opportunities and global markets through online platforms and the ability to engage with new art forms such as digital painting, animation, and multimedia art. This expansion of art has provided artists with the opportunity to reach a wider audience and diversify their creative output. However, the research also highlights the significant challenges freelance artists face, as the art market today is increasingly facing threats to its survival due to a lack of resources, increasing competition, and digital reproduction. Additionally, the research examines the impact that the technology sector is having on traditional art. The paper also examines the educational pathways available for aspiring digital artists in India and assesses the effectiveness of government policies and initiatives aimed at supporting the digital arts sector. It also provides practical insights for freelance artists to pursue an emerging market and enhance their professional success. Overall, the study presents a comprehensive analysis of how digital technology has reshaped freelance art in India, examines both the benefits and barriers presented in this dynamic sector, and suggests potential directions for future development.